Evaluation the Suitability of Saliva for DNA Profiling Analysis in Comparative with Blood Samples. - Namaa, Dhuha Salim (Al-Nahrain Journal of Science, 2018)
Collection, preservation and analysis of body fluids are important aspect of forensic science. Isolated DNA from saliva has become an attractive alternative to the use of blood-derived DNA in performance characteristics. The objectives of this study were to determine the suitability of saliva for DNA profiling analysis and compare blood and saliva as biological source in the performance characteristics. Saliva and buccal swab (as the reference source of genomic DNA) samples were collected from 7 healthy volunteers. The saliva samples were taken with different volumes (100, 200, 300, 400) μl of whole saliva. On the other hand, blood and saliva samples were collected from 25 healthy volunteers in a comparative study. Extraction of DNA was done by Phenol Chloroform method. The results showed difference in the mean DNA concentration which was quantified by using Real-Time PCR from various volumes of saliva samples (100, 200, 300, 400) μl recording (1.23, 2.21, 3.40, 8.24) ng / μl respectively. The mean allele’s percentage of 15 STR loci that appeared in profile of different volumes mentioned above were (73.3, 83.7, 89.5, 99.04)% respectively. The mean DNA concentration and the purity from saliva and blood samples were measured by using nonadrop spectrophotometer recording (10.736, 51.164) ng/ μl (1.64, 1.72) respectively. It is concluded that, saliva samples can be taken at different volumes in the field of criminal research instead of the traditional a way of taking blood samples.